KAJIAN SOSIOLOGI PERAN MEDIA SOSIAL DALAM PENEGAKAN HUKUM DI INDONESIA - Waqingatul Hidayah, Yola (Negara dan Keadilan, 2018)
Along with the development of advances in technology and information, the existence of social media has had positive and negative impacts on its users. In the modern era where everyone uses social media, an unlawful act is likely to quickly go viral. Internet users can easily follow case developments, provide support to victims and their families, or even gather support from netizens to oversee justice. Monitoring cases by internet users can put pressure on authorities to take appropriate action to uphold justice. The function and role of social media in law enforcement in Indonesia is to act as social control, namely by providing criticism, correction, supervision and suggestions, as well as encouraging the realization of the supremacy of the law, so that the positive impact of this function is that law enforcers will be able to optimize the implementation of handling unlawful acts. in accordance with statutory regulations.